A cation exchange based electrochemical sensor for cetyltrimethylammonium bromide detection using an acridine orange/polystyrene sulfonate system1. Issue 9 (7th May 2015) - Hao, Xia; Xu, Zhen; Li, Na; Li, Nian Bing; Luo, Hong Qun
<x xml:space="preserve">Abstract</x> A novel electrochemical sensor for the detection of quaternary ammonium surfactants has been developed based on the cation exchange mechanism using an AO/PSS/PEI modified glassy carbon electrode.